URGENSI MAHKAMAH KONSTITUSI SEBAGAI PERADILAN NORMA (Lex Jurnalica, 2017)
AbstractThe authority of the norms (legislation) test in the Unitar y State of the Republic of Indonesia is held by two judicial institutions namely the Supreme Court which examines the laws and regulations under the Act against the Act. And the Constitutional Court is testing the Act against the Constitution. This study aims to describe the philosophical background of the establishment of the Constitutional Court and the urgency of the Constitutional Court as the judicial norm. This research is a normative legal research that will search and collect and analyze qualitative legal materials of primary law material and secondary legal material in juridical, historical, comparative, and political. The results show that the rear of philosophical formation of the Constitutional Court is in order to maintain and sustain the people's sovereignty. The Urgency of the Constitutional Court as the judicial norm is a constitutional requirement to provide assurance of legal certainty and justice and as a consequence of the hierarchy theory of legal norm in Indonesian legal system.Keywords: urgency, constitutional court, norm courtAbstrakKewenangan pengujian norma (peraturan perundang-undangan) di Negara Kesatuan Republik Indonesia dipegang oleh dua lembaga peradilan yakni Mahkamah Agung yang menguji peraturan perundang-undangan di bawah Undang-Undang terhadap Undang-Undang. Dan Mahkamah Konstitusi yang menguji Undang-Undang terhadap Undang-Undang Dasar. Penelitian ini bertujuan untuk mendeskripsikan latar belakang filosofis pembentukan Mahkamah Konstitusi dan urgensi Mahkamah Konstitusi sebagai peradilan norma. Penelitian ini adalah penelitian hukum normatif yang akan mencari dan mengumpulkan serta menganalisa bahan-bahan hukum secara kualitatif bahan hukum primer dan bahan hukum sekunder secara yuridis, historik, komparatif, dan politis. Hasil penelitian menunjukkan bahwa latar belakang filosofis pembentukan Mahkamah Konstitusi adalah dalam rangka menjaga dan mempertahankan kedaulatan rakyat. Urgensi Mahkamah Konstitusi sebagai peradilan norma merupakan kebutuhan konstitusional untuk memberikan jaminan kepastian hukum dan keadilan serta sebagai konsekuensi atas dianutnya teori hirarki norma hukum dalam sistem hukum Indonesia. Kata kunci: urgensi, mahkamah konstitusi, peradilan norma